2024
DOI: 10.1073/pnas.2316394121
|View full text |Cite
|
Sign up to set email alerts
|

Network physics of attractive colloidal gels: Resilience, rigidity, and phase diagram

Mohammad Nabizadeh,
Farzaneh Nasirian,
Xinzhi Li
et al.

Abstract: Colloidal gels exhibit solid-like behavior at vanishingly small fractions of solids, owing to ramified space-spanning networks that form due to particle–particle interactions. These networks give the gel its rigidity, and with stronger attractions the elasticity grows as well. The emergence of rigidity can be described through a mean field approach; nonetheless, fundamental understanding of how rigidity varies in gels of different attractions is lacking. Moreover, recovering an accurate gelation phase diagram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Real-time measurements serve as a valuable tool to unravel the kinetics and mechanisms governing these transitions, facilitating improved control and predictability ( 26 , 27 ). Consequently, it becomes imperative to develop robust in situ tools and analysis models that enable us to investigate the dynamic behavior of complex materials ( 28 , 29 ), validate theoretical constructs ( 30 , 31 ), and engineer functional materials for a variety of applications within these soft matter systems.…”
mentioning
confidence: 99%
“…Real-time measurements serve as a valuable tool to unravel the kinetics and mechanisms governing these transitions, facilitating improved control and predictability ( 26 , 27 ). Consequently, it becomes imperative to develop robust in situ tools and analysis models that enable us to investigate the dynamic behavior of complex materials ( 28 , 29 ), validate theoretical constructs ( 30 , 31 ), and engineer functional materials for a variety of applications within these soft matter systems.…”
mentioning
confidence: 99%
“…By comparing colloidal structures formed with [slightly] non-uniform interactions to those with ideally uniform ones, we isolate the influence of spatial interaction variation on the overall gel structure morphology. Previous studies have shown that at the very weak attraction limits of u 0 = 3–4 k B T , inherent structural heterogeneities of the colloidal gels are most visible; 11,26,32,33 however, there also exist inconsistencies between the experimentally observed structures and computationally modeled ones at these limits. Thus, here, we conduct simulations at two average attraction strengths, u 0 = 6 k B T and 12 k B T , representing weak and strong gels.…”
Section: Introductionmentioning
confidence: 99%
“…6–9 Emergence of elasticity in colloidal gels is believed to be directly governed by the characteristics of their underlying particulate structure. 10–12 Recent work on the characterization of the mesoscale description of colloidal gels shows that the size and inter-connectivity of clusters play a major role in the load-bearing ability of the overall structure. 11 Hence, different factors that change the cluster-level characteristics of the particle network can potentially impact the overall mechanics of the gel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation